Z osobliwości językowych warsztatu przekładowego Biblii brzeskiej (zagadnienia wybrane) - Koziara, Stanisław (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2017)
This paper is an attempt at drawing attention to the first Protestant translation of the whole Bible into Polish, which is traditionally known as Brest Bible or Radziwill Bible, in terms of its significance and place in the history of Polish language. The first part of this work is the introduction of some basic data from the field of origins, history and the state of previous philological research into Brest Bible. The second part of the paper shows the role of the translation in the process of shaping the characteristics of Polish biblical style and the way in which the translators used the richness and potential of the Polish language in the Renaissance. As the source material to complete the research task the author of the paper used some chosen areas of the language in Brest Bible, which included lexis and fixed expressions.